Jenis Tanaman untuk Meningkatkan Fungsi Ekosistem pada Program Reklamasi Lahan Bekas Tambang di Provinsi Kalimantan Selatan - Soeleman, Guritno; Amin, Radjali; Fandeli, Chafid (Universitas Gadjah Mada, 2026)
Mined reclamation failure could lead to land degradation, ecosystem instability, community poverty, and loss of environmental services. Previous research linked reclamation success to the selection of suitable plants. This study aimed to identify the best species for reclamation and ecosystem services, measured by ecosystem conditions, plant growth, and soil fertility. Angsana (Pterocarpus indicus Willd.), waru (Hibiscus tiliaceus L.), cashew (Anacardium occidentale L.), sengon (Paraserianthes falcataria (L.) Nielsen), and mahogany (Swietenia mahagoni (L.) Jacq.) were selected as the highest number of species planted in PT Kalimantan Energi Lestari (KEL) reclamation area. Mean annual increment (MAI) was measured using a 10% sampling intensity for all plant stages. Soil quality (C-organic, N, C/N, P, K) was sampled at 5% around the tree root zone using a purposive sampling method. The five species showed positive impacts on soil nutrients, increasing by 14.6% in five-year-old plants, except for K-exchange, which decreased by 3.4% to 71.4%. In addition, P. falcataria improved significantly in three macro parameters, namely C-organic 121.2%, N-total 100%, and P-avail 156%, and had the highest MAI for total height of 252.5 cm/year. This research concluded that P. falcataria was the most appropriate revegetation plant species for the reclamation program in coal-mined areas